Minsky's approach to employment policy and poverty: employer of last resort and the war on poverty - L. Randall Wray (Levy Economics Institute of Bard College, 2007)
While Hyman P. Minsky is best known for his work on financial instability, he was also intimately involved in the postwar debates about fiscal policy and what would become the War on Poverty. Indeed, at the University of California, Berkeley, he was a vehement critic of the policies of the Kennedy and Johnson administrations, and played a major role in developing an alternative. Minsky insisted that the high investment path chosen by postwar fine-tuners would generate macroeconomic instability, and that the War on Poverty would never lower poverty rates significantly. In retrospect, he was correct on both accounts. Further, he proposed high consumption and an employer of last resort policy as essential ingredients of any coherent strategy for achieving macro stability and poverty elimination. This paper summarizes Minsky's work in this area, focusing on his writings from the early 1960s through the early 1970s in order to explore the path not taken. Keywords: Hyman Minsky ; Employment and Poverty ; Employer of Last Resort ; War on Poverty ; Regional and Sectoral Disparities ; Financial Instability
Keywords: E24; E61; J68; R11; 330